Influence of Professional Skepticism and Adherence to Code of Ethics on Fraud Disclosure - Amiruddin, Ardiansyah; Adang, Ferry (International Journal of Multidisciplinary Approach Research and Science, 2024)
This research was conducted to analyze the influence of the variables of professional skepticism and adherence to the code of ethics on the quality of audit results. The subjects of this study were 65 auditors working at the Representative Office of the BPK in Papua Province. The research method used in this study is the causality research method. The data collected in this study is primary data obtained through questionnaires distributed to each auditor. The data analysis method used is multiple regression analysis. The results of this study can be concluded as follows: (1) Based on partial test results, professional skepticism has a positive and significant effect on fraud disclosure. (2) Based on partial test results, adherence to the code of ethics does not affect fraud disclosure. (3) Professional skepticism and adherence to the code of ethics have a simultaneous effect on fraud disclosure.